Family counselling in the context of crisis cause by children behavioral disorders - Díaz Pupo, Arledys (Transformación, 2024)
Objective: This article aims to argue theoretical-conceptual enclaves of the family, which underpin the practice of educational guidance in addressing normative and paranormative crises.Methods: The systematization of previous scientific results from various authors was used, as well as the recording of teaching activities, training sections on methods, and educational research experiences in the Pedagogy Psychology major.Result: Theoretical foundations of the family in crisis are provided, useful for this scientific endeavor. An analysis of behavioral disorders is presented. Specific theoretical references are developed that underpin the proposal of guidance based on the Historical-Cultural Approach as an option in assisting families in crisis for the effective management of behavioral disorders in adolescents.Conclusion: Educational guidance based on the Historical-Cultural Approach represents an option for assisting families in crisis in effectively managing behavioral disorders in adolescents.
Keywords: family; family education; family counselling; behavior problems